A Compact Broadband Common-Aperture Dual-Polarized Antenna for Drone Applications - Xue-Ping Li; Chao-Liang He; Jun-Fei Ji; Meng-Bing Yang; Yan Zhang; An-Xue Zhang; Wei Li (Micromachines)
A novel common-aperture miniaturized antenna with wideband and dual-polarized characteristics is proposed, which consists of a circularly polarized (CP) and a linearly polarized (LP) antenna. The circularly polarized antenna stacked on the upper layer adopts asymmetrical ground and introduces the patch and T-type feed network. On this basis, the meshed reflector structure, which also works as a ground plane for the LP antenna, is added to reduce the influence on circular polarization and achieve directional radiation. The LP antenna stacked in the lower layer uses a monopole structure, and the coaxial feed line perforates the reflector, and thereby the common-aperture antennas are tightly stacked together from top to bottom. Simulation and test are in good accordance, and the results show that the two ports of the antenna are well matched in the range of 5.5 GHz to 7.8 GHz, where peak gains of 8.5 dB and 6 dB are realized for circular polarization and linear polarization, respectively. Moreover, the 3 dB axial ratio (AR) bandwidth of the CP antenna is 34.3% and the isolation between the two ports is better than 15 dB, suggesting potential applications in the relay platform or drone detection for signal transmission and reception.